The need for national leadership, partnerships and programmes to promote the health and well-being of looked-after children in Scotland - Steven McCluskey (Scottish Journal of Residential Child Care)
Looked-after children and young people are a group whose backgrounds and care experiences have led them to be described as one of the most socially excluded and disadvantaged groups in society. Despite the fact that looked-after children are identified as having a range of complex and unmet health needs, the evidence presented suggests these young people are disadvantaged in accessing universal and specialist health services. Evidence further indicates that social exclusion, disaffection and powerlessness are shared features of the lives of looked-after children, due to institutional and interpersonal dependence upon socially constructed and adult-controlled systems of care and protection.